Winter University 2016 - Yamova, Eugenia; Nuyanzina, Valeria (project baikal, 2016)
The article reviews the results of the 17th session of International Baikal Winter University of Urban Planning Design, the subject of which was “The System of Urban Centers. Formation of Public Spaces”. The international teams presented their reconstruction projects for urban areas, including periphery districts of Irkutsk. The teams proposed various scenarios for using the public spaces in different time, by different categories of users, depending on the functions of public spaces.